ANALYSIS OF TRAIN VIBRATION AND NOISE ON POPULATION SUBJECTIVE COMPLAINTS - Fitria Ade Alfira; Khambali Khambali; Suprijandani Suprijandani; Ernita Sari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Passing trains causes vibration and noise, the Ministry of the environment monitors noise and vibration of trains getting results 100% exceeding the quality standards carried out in four big cities. This study aimed to determine the analysis of train vibration and noise on subjective complaints of residents of Bringinbendo Village. This type of research used descriptive research with a cross sectional approach. The population used was housewives who were in the Bringinbendo Village area, especially in RW 04 (RT 07, RT 09) and RW 07 (RT 10, RT 12) Taman District, Sidoarjo Regency as many as 132. The sample used was 99 housewives who taken by simple random sampling method. Data analysis was carried out descriptively to describe the data. The vibration measurement at point 1 is 2.1 Hz and at point 2 is 1 Hz, both points were still below the standard vibration level, while the noise measurement at point 1 is 75.95 dB(A) and at point 2 is 70.56 dB( A) the value exceeds the specified noise quality standard. Subjective complaints obtained from interviews were 63.6% had complaints and 36.4% had no complaints. The vibration and noise of the train can caused residents to experience subjective complaints. People should exercise control in their homes to reduce the noise of the train. Keywords: train, vibration, noise